2011
DOI: 10.1002/j.0022-0337.2011.75.5.tb05088.x
|View full text |Cite
|
Sign up to set email alerts
|

Socialization of New Dental Therapists on Entering the Profession

Abstract: Dental therapy is relatively new in the United States. This qualitative study examines the experiences and impressions of the inaugural class of the irst dental school-based dental therapy program in the United States. A grounded theory design using open-ended interviews and focus groups was carried out with the nine students in the class at the beginning of their program and after the fall and spring semesters of their irst year. Student responses were audiotaped, transcribed verbatim, and presented to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Therefore, while our survey did not directly measure dental students’ attitudes about working with dental therapists, another survey conducted at our school among the same dental students reported on factors that could directly affect the dental team working environment 10 . Those results indicated that some dental students worried about dental therapists’ scope of practice and how it would affect their dental practice in the future 30 . These dental students, while indicating a slightly positive attitude about differentiating professional roles through intraprofessional training, had neutral or negative opinions about both dental therapists’ efficacy in dental public health programs and the public's anticipated acceptance of dental therapists as oral health care providers 15 .…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, while our survey did not directly measure dental students’ attitudes about working with dental therapists, another survey conducted at our school among the same dental students reported on factors that could directly affect the dental team working environment 10 . Those results indicated that some dental students worried about dental therapists’ scope of practice and how it would affect their dental practice in the future 30 . These dental students, while indicating a slightly positive attitude about differentiating professional roles through intraprofessional training, had neutral or negative opinions about both dental therapists’ efficacy in dental public health programs and the public's anticipated acceptance of dental therapists as oral health care providers 15 .…”
Section: Discussionmentioning
confidence: 92%
“…A key feature of the Minnesota model is the adoption of restrictions to ensure that DTs practice in settings that serve low‐income and underserved individuals. An essential aspect of Alaska's DHAT is that DTs are recruited from the rural communities where they serve.…”
Section: Discussionmentioning
confidence: 99%